Tudor Staphylococcal Nuclease Links Formation of Stress Granules and Processing Bodies with mRNA Catabolism in Arabidopsis - Gutierrez-Beltran, Emilio (Plant Cell, 2015)
Tudor Staphylococcal Nuclease (TSN or Tudor-SN; also known as SND1) is an evolutionarily conserved protein involved in the transcriptional and posttranscriptional regulation of gene expression in animals. Although TSN was found to be indispensable for normal plant development and stress tolerance, the molecular mechanisms underlying these functions remain elusive. Here, we show that Arabidopsis thaliana TSN is essential for the integrity and function of cytoplasmic messenger ribonucleoprotein (mRNP) complexes called stress granules (SGs) and processing bodies (PBs), sites of posttranscriptional gene regulation during stress. TSN associates with SGs following their microtubule-dependent assembly and plays a scaffolding role in both SGs and PBs. The enzymatically active tandem repeat of four SN domains is crucial for targeting TSN to the cytoplasmic mRNA complexes and is sufficient for the cytoprotective function of TSN during stress. Furthermore, our work connects the cytoprotective function of TSN with its positive role in stress-induced mRNA decapping. While stress led to a pronounced increase in the accumulation of uncapped mRNAs in wild-type plants, this increase was abrogated in TSN knockout plants. Taken together, our results establish TSN as a key enzymatic component of the catabolic machinery responsible for the processing of mRNAs in the cytoplasmic mRNP complexes during stress.